Electrospun Biocompatible Poly (e-caprolactonediol)Based Polyurethane Core/Shell Nanofibrous Scaffold for Controlled Release of Temozolomide - Irani, Mohammad; Sadeghi, Gity Mir Mohamad; Haririan, Ismaeil
The electrospun biocompatible poly (e-caprolactonediol)based polyurethane (PCL-Diol-b-PU)core/shell nanofibrous scaffolds were prepared via the coaxial electrospinning process. Temozolomide (TMZ)as an anticancer drug was loaded into the core of fibers to control the release of TMZ for the treatment of glioblastoma. The properties of nanofibers were characterized using XRD, FTIR, SEM and TEM analysis. The sustained delivery of TMZ without initial burst release was achieved from all prepared core-shell nanofibrous samples over 30 days. The cytotoxicity results revealed that the TMZ loaded PCL-Diol-b-PU core-shell nanofibers could be used as a drug delivery implant to deliver TMZ against glioblastoma tumors.
Keywords: CORE-SHELL; NANOFIBER; PCL-DIOL-B-PU; SUSTAINED DELIVERY; TEMOZOLOMIDE